Immobilization of Enzymes and Cells Methods and Protocols - Guisan, Jose M.; Bolivar, Juan M.; López-Gallego, Fernando; Rocha-Martín, Javier (Methods in Molecular Biology, 2020)
XVI, 495 p. 198 illus., 109 illus. in color.